Analysis of Islamic Psychology Student Research Trends for the Preparation of Study Program Research Roadmap - Triyono Triyono; Wakhid Musthofa; Adzillina Zam Zam Desertyarani; Nureyzwan Sabani (Al-Qalb : Jurnal Psikologi Islam, 2026)
This study aims to comprehensively analyze the overview of research trends among Islamic Psychology students of UIN Raden Mas Said Surakarta for the 2021–2023 period based on research types, areas of psychological interest, and research topics, and to use these trends as considerations in developing the study program’s research roadmap for 2025–2034. This study employs a mixed-method approach. Quantitative data were obtained from students’ final project documents (theses) submitted to the Library of the Faculty of Ushuluddin and Da’wah during 2021–2023. Qualitative data were collected from students and lecturers selected through stratified purposeful sampling. The results show that the qualitative approach is the most dominant. In terms of research interest, social studies are the most preferred field, while resilience is the most frequently researched topic. These findings serve as a basis for developing the research roadmap for 2025–2034, which emphasizes the leading theme of Islamic Psychology, Mental Health, and Well-being. It is recommended that future research should focus more on strengthening the substantive core of Islamic psychology, particularly in terms of variables and research themes grounded in Islamic psychological perspectives, rather than merely focusing on research objects. In addition, integrating quantitative approaches across various branches of psychology is encouraged to provide a more comprehensive and holistic understanding.